Effectiveness of bonus and penalty incentive contracts in supply chain exchanges: Does national culture matter?. Issue 1 (24th October 2018) - Lee, Yun Shin; Ribbink, Dina; Eckerd, Stephanie
Abstract : In this study, we investigate the impact of national culture on the effectiveness of bonus and penalty incentive contracts in supply chain exchanges. We conducted laboratory experiments in Canada, China, and South Korea, involving transactional exchanges in which suppliers were presented with either bonus or penalty contracts. Then we compared suppliers' contract acceptance, level of effort, and shirking across national cultures. Our findings reveal critical cultural influences on contract effectiveness. We show that although acceptance of bonus contracts is comparable across cultures, suppliers from Canada, a national culture considered low in power distance and high in humane orientation, exhibit lower acceptance rates of penalty contracts. In addition, we find evidence that suppliers associated with collectivist cultures exert more effort and shirk less in bonus contracts but these relationships also are more complex. When we compare contract effectiveness across bonus and penalty contracts within a given cultural setting, we find in all three countries greater acceptance of bonus contracts than penalty contracts. Also, after contracts are accepted, bonus contracts are more successful in China because suppliers exert greater effort and shirk less under bonus contracts than penalty contracts. However, in Canada and South Korea, the results of accepted contracts for both penalty and bonus contracts are nearly indistinguishable.